Assessment of Quality and Technique in Receptive Language Skill in Retelling News in Javanese: Systemic Functional Linguistics Approach - Chalimah Chalimah; Yesi Aprilia Yunanda (Javanologi: International Journal of Javanese Studies, 2023)
Finding solution in society in ‘Banjaragung Village’ in East Java seems that the people mostly use Indonesian in official meeting in the event of PKK and even many people prefer using Indonesian than Javanese. This research is conducted to see how good the society in retelling news by using Javanese as well as the technique to see the level of receptive language analyzed with systemic functional linguistics. It can also see how the society maintains Javanese as character principle. The research is done in some steps, namely: giving short materials or pre-knowledge about receptive skill and theory of complex thinking in systemic functional linguistics theory; giving retelling news test; and analyzing as well as reporting the findings to find out the patterns which are used. The findings show that the receptive language skill in society in ‘Banjaragung Village’ in East Java tend to be high as much as 77,85% that can retell the news well in complex clauses by using Javanese.Keywords: Assessment, Receptive Skill, Retelling News, Javanese